CONFLICT OF RELATIONS BETWEEN GENGHIZ KHAN AND MUHAMMAD KHOREZMSHAH (TAMADDUN NURI JURNALI, 2025)
This article discusses the diplomatic relations between Khorezmshah Muhammad and Genghis Khan at the beginning of the 13th century, the Utrar tragedy, and the impact of these events on the fate of the entire region. The internal conflicts of the Khorezmshah state, the political intrigues of Turkan Khotun, as well as Genghis Khan's skillful diplomacy and military campaigns are analyzed. Also, the tragic consequences of the wrong decisions and shortsightedness of Khorezmshah Muhammad are considered based on historical sources.